Development of Islamic Religious Education in a Multicultural Society - Ardian, Ardian; Qur'aniyul Farid, Muh. Jillul (JUPE : Jurnal Pendidikan Mandala, 2025)
Islamic religious education in society is very important. Through education and teaching, it has an impact on good morals. Religious teachings are not merely rituals but also the actualization of religious teachings and values in everyday life. This paper aims to determine and discuss the development of Islamic religious education in society. The writing method is a literature review with a descriptive and exploratory approach. It can be concluded that the development/instillation of Islamic religious education values in society in an effort to improve the quality of faith includes (1) religious/faith education; (2) religious education that will be taught to children to build a young generation that is committed and accustomed to carrying out worship such as prayer, fasting, reading the Qur'an, and (3) moral education.